Internal and External Drivers of Online Impulsive Buying Behavior and Post-purchase Cognitive Dissonance: A Confirmatory Factor Analysis on 284 Egyptians’ online Shoppers - Amira G. AHMED; Ahmed Y. EBEID; Mahmoud F. MOHAMED (Communications of International Proceedings, 2024)
The current study proposes an integrated framework that combines several factors influencing online impulsive buying behavior, and how online shoppers feel after making online purchases. This study is a response to the growth of online shopping, which has become a prevalent behavior among online shoppers in the emerging economies. However, there is a lack of research on this subject in the emerging markets. Also, prior research examined the current study constructs individually. As a result, this study seeks to examine both internal factors (fear of missing out and social media addiction) and external factors (promotional activities and online visual merchandising) that lead to online impulsive buying behavior among customers in Egypt.  In addition, the study tested the impact of online impulsive buying behavior on post-purchase cognitive dissonance. The hypothesized model was tested using structural equation modelling (SEM) based on data obtained from 284 Egyptian individuals who shopped online and filled out a self-administered online questionnaire. Findings revealed that fear of missing out, social media addiction, and promotional activities had a significant positive effect on online impulsive buying behavior. However, online visual merchandising was not found to have a significant effect on online impulsive buying behavior. Furthermore, online impulsive buying behavior directly and significantly impacts post-purchase cognitive dissonance. This study tried to explain online impulsive buying behavior in the Egyptian society. In addition, it provided insights for academicians and marketers to help them understand customer behavior.
Keywords: Drivers of online impulsive buying; online impulsive buying behavior; post-purchase cognitive dissonance; Egypt.